Pressure groups in Indian politics - "Fadia, Babulal" (New Delhi, 1980)
One of the dominant trends in contemporary political science culminates in emphasis on informal factors, the dynamic nature of the political process, the role of private groups, the impact of society and culture on politics.
Keywords: Pressure groups